PENERAPAN ELECTRONIC GOVERNMENT DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KABUPATEN LUWU - Halim, Tiara; Hakim, Lukman; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to find out how electronic government is implemented in population administration services at the Luwu Regency Population and Civil Registration Service in the aspects of support, capacity and value. The method in this research uses qualitative research methods with descriptive research type. The results of this research indicate that the implementation of electronic government in population administration services at the Population and Civil Registration Service of Luwu Regency is in the good category. However, analysis shows that the implementation of electronic government in population administration services has not been fully implemented, such as making family cards, birth certificates, death certificates, marriage certificates and other population certificates because people prefer to register manually rather than online because the website is still in progress. improvements and people who are not used to using information technology are reluctant to access the websites provided and prefer to meet face to face if they need services.